Dye-Sensitized Solar Cells with Anatase TiO2 Nanorods Prepared by Hydrothermal Method. (23rd October 2013) - Jeng, Ming-Jer; Wung, Yi-Lun; Chang, Liann-Be; Chow, Lee
Abstract : The hydrothermal method provides an effective reaction environment for the synthesis of nanocrystalline materials with high purity and well-controlled crystallinity. In this work, we started with various sizes of commercial TiO2 powders and used the hydrothermal method to prepare TiO2 thin films. We found that the synthesized TiO2 nanorods were thin and long when smaller TiO2 particles were used, while larger TiO2 particles produced thicker and shorter nanorods. We also found that TiO2 films prepared by TiO2 nanorods exhibited larger surface roughness than those prepared by the commercial TiO2 particles. It was found that a pure anatase phase of TiO2 nanorods can be obtained from the hydrothermal method. The dye-sensitized solar cells fabricated with TiO2 nanorods exhibited a higher solar efficiency than those fabricated with commercial TiO2 nanoparticles directly. Further, triple-layer structures of TiO2 thin films with different particle sizes were investigated to improve the solar efficiency.